The Guides Verbs in the Arabic Language: Are Its Terms Originals or Borrowed? - Khadidja, Safi (Universitas Muhammadiyah Sumatera Barat, 2021)
Grammarists differed about the definition of the verb in the Arabic language, but they were in great agreement in dividing it from different sides. From these sides, we find the division of verbs according to the function of directing, which is the subject of this study. The view of the ancient grammarians to the function was affected by the grammatical direction followed (factor theory, semantics). It was noted in some of what they termed a clear dimension of the function of guidance, and with reference to the global grammar that created entrances between languages, even if the characteristics of languages differed among them, borrowing as a mechanism of linguistic development of the Arabic language has allowed, based on this way, to borrow many terms from Other languages were -sometimes- more compatible than that we find in the Arabic language used, for this reason, the researcher tried to study the guides verbs in the Arabic language; After enumerating them and clarifying their terms in the Arabic language, then comparing them with what is used in the French and English languages; It was found that some of the guides Arabic verbs were labeled with a term that is a sign of this function, and some of them were affected by the factor theory in grammar, so their terms did not express the function of directing, and after compare them with modern Arabic studies ,and also, in English and French, we were able to find an appropriate term to achieve the concept of directing. Therefore, the researcher suggested updating or changing these terms by creating appropriate terms that take advantage of the English and French languages, as well as modern Arabic conventions..